A simple but reliable method for measuring 3D Achilles tendon moment arm geometry from a single, static magnetic resonance scan. (11th April 2017) - Alexander, C.F.; Lum, I.; Reid, S.; Clarke, E.; Stannage, K.; El-Sallam Abd, A.; Herbert, R.D.; Donnelly, C.J.
Abstract: Current methods for measuring in vivo 3D muscle-tendon moment arms generally rely on the acquisition of magnetic resonance imaging (MRI) scans at multiple joint angles. However, for patients with musculoskeletal pathologies such as fixed contractures, moving a joint through its full range of motion is not always feasible. The purpose of this research was to develop a simple, but reliable in vivo 3D Achilles tendon moment arm (ATMA) technique from a single static MRI scan. To accomplish this, for nine healthy adults (5 males, 4 females), the geometry of a cylinder was fit to the 3D form of the talus dome, which was used to estimate the talocrural flexion/extension axis, and a fifth-order polynomial fit to the line of action of the Achilles tendon. The single static scan in vivo 3D ATMA estimates were compared to estimates obtained from the same subjects at the same ankle joint angles using a previously validated 3D dynamic MRI based in vivo ATMA measurement technique. The ATMA estimates from the single scan in vivo 3D method (52.5 mm ± 5.6) were in excellent agreement (ICC = 0.912) to the validated in vivo 3D method (51.5 mm ± 5.1). These data show reliable in vivo 3D ATMA can be obtained from a single MRI scan for healthy adult populations. The single scan, in vivo 3D ATMA technique provides researchers with a simple, but reliable method for obtaining subject-specific ATMAs for musculoskeletal modelling purposes.